Awareness of users and motivational factors for using new psychoactive substances in Belgium - Sarah Simonis; Michaël Canfyn; Anton Van Dijck; Tina Van Havere; Eric Deconinck; Peter Blanckaert; Lies Gremeaux (BMC, 2020)
Abstract Background Few data on motivations for using new psychoactive substances (NPS) are available. However, the cost, the legal status, and their accessibility through channels like internet contributed to the popularity of NPS. The objective of this article are first to gain a deeper understanding of the culture surrounding NPS in Belgium and second to define the awareness of the users concerning the content of the NPS they are consuming. Methods Snowball sampling and partners in the drug demand reduction field were used as a gateway in order to reach a heterogeneous study population. In total, 45 users were recruited and in-depth interviews were conducted. The personal experiences of NPS users and their needs for support along the continuum of care were explored through an interview guideline, while subjects were given the opportunity to deposit a NPS sample for forensic analysis in a recognized laboratory. Results A diversity of profiles was found among NPS users but also a wide diversity in the motives to consume NPS: personal reasons such as pleasure, mind exploration, being connected to others, or out of curiosity, but also external reasons such as price, accessibility or the specific effects procured by certain NPS. The results showed as well that a majority of NPS users seem to be aware of the substances they are using. Conclusion Understanding the motivations of use is of importance to determine which type of NPS targeted interventions are adapted to different profiles of users.